Advertisement Remove all ads

Solve: 13(X - 4) - 3(X - 9) - 5(X + 4) = 0 - Mathematics

Sum

Solve: 13(x - 4) - 3(x - 9) - 5(x + 4) = 0 

Advertisement Remove all ads

Solution

13(x - 4) - 3(x - 9) - 5(x + 4) = 0 

⇒ 13x - 52 - 3x + 27 - 5x - 20 = 0

⇒ 13x - 3x - 5x - 52 + 27 - 20 = 0

⇒ 13x - 8x - 72 + 27 = 0

⇒ 5x - 45 = 0

Dividing by 5,

`"5x"/5 - 45/5 = 0 => "x" - 9 = 0 => x = 9`

Verification:

L.H.S. = 13(x - 4) -3(x - 9) - 5(x + 4)

= 13(9 - 4) - 3(9 - 9) - 5(9 + 4)

= 13 × 5 - 3 × 0 - 5 × 13

= 65 - 0 - 65 = 0 = R.H.S.

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Selina Concise Mathematics Class 8 ICSE
Chapter 14 Linear Equations in one Variable
Exercise 14 (C) | Q 1.05 | Page 169
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×